2014
DOI: 10.1126/scitranslmed.3007323
|View full text |Cite
|
Sign up to set email alerts
|

Intramuscular Therapeutic Vaccination Targeting HPV16 Induces T Cell Responses That Localize in Mucosal Lesions

Abstract: About 25% of high-grade cervical intraepithelial neoplasias (CIN2/3) caused by human papillomavirus serotype 16 (HPV16) undergo complete spontaneous regression. However, to date, therapeutic vaccination strategies for HPV disease have yielded limited success when measured by their ability to induce robust peripheral blood T cell responses to vaccine antigen. We report marked immunologic changes in the target lesion microenvironment after intramuscular therapeutic vaccination targeting HPV16 E6/E7 antigens, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
170
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 203 publications
(179 citation statements)
references
References 43 publications
7
170
0
2
Order By: Relevance
“…Indeed, HPV16 synthetic long peptides used within conventional vaccination approaches induced strong antitumor immunity and clinical responses in patients with HPV16-driven carcinomas (50)(51)(52). More recently, neoantigen vaccines in the form of RNA polyepitopes or based on the use of synthetic long peptides administered with adjuvant were shown to elicit robust specific T cell responses to advanced melanoma, with potential clinical benefits (53,54).…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, HPV16 synthetic long peptides used within conventional vaccination approaches induced strong antitumor immunity and clinical responses in patients with HPV16-driven carcinomas (50)(51)(52). More recently, neoantigen vaccines in the form of RNA polyepitopes or based on the use of synthetic long peptides administered with adjuvant were shown to elicit robust specific T cell responses to advanced melanoma, with potential clinical benefits (53,54).…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, in melanoma, breast, lung, and colorectal carcinomas, high densities of TLSs have been reported to correlate with a favorable prognosis (36). Strikingly, TLSs are induced in cervical carcinomas (37) or pancreatic ductal cancer (38) upon vaccination with TSMAs. That TLSs are necessary for generating clinically efficient immune reactions is supported by the fact that a high density of CD8 + T cells is associated with longer patient survival when tumors display high TLS densities in lung (39), colorectal (40), and renal cell cancers (41).…”
Section: Cancer Immunoediting: From Mice To Humansmentioning
confidence: 99%
“…In the vast majority of cancers, tumor infiltration by CD8 þ memory cytotoxic T cells and Th1 cells is associated with good clinical outcome (1). In addition, it has been reported that an organized local immune reaction, characterized by the presence of mature dendritic cells (DC) localized in tumor-associated tertiary lymphoid structures (TLS), is necessary to orchestrate this cytotoxic and Th1 immune contexture and is associated with good clinical outcome (3)(4)(5)(6)(7)(8) and response to therapeutic vaccines (9,10). However, several recent findings challenge this concept of the unequivocal relation of effector memory CD8 þ T-cell infiltration with a good clinical outcome in cancer.…”
Section: Introductionmentioning
confidence: 99%